Enhancing Civic Knowledge Through an Immersive Virtual Reality Museum: Development and Effectiveness of Bumantara.edu in Indonesian Civic Education - Ahmad Amru Asy Syafiq; Didik Sukriono; Nuruddin Hady (The Eastasouth Journal of Learning and Educations, 2026)
Indonesian schools have adopted one-to-one tablet programmes rapidly, but the devices meant to support learning now compete with it for attention. This study developed and evaluated Bumantara.edu, a tablet-deployed Virtual Reality (VR) museum with an integrated AI chatbot tutor, built to strengthen Civic Knowledge in the national-movement history strand of Pancasila and Civic Education (PPKn). Using an ADDIE-based Research and Development design, the product was assessed by a content expert, a media expert and the class teacher, then tested with 25 eighth-grade students at SMP Thursina IIBS Malang through a one-group pretest–posttest design with a 20-item higher-order thinking instrument (Cronbach's α = .812). Validation reached 89% for content and 97% for media, and practicality 91% from the teacher and 88.20% from students. Civic Knowledge rose from M = 53.40 (SD = 21.59) to M = 88.60 (SD = 3.69), a mean normalised gain of 0.70, and after Shapiro–Wilk indicated non-normality a Wilcoxon signed-rank test confirmed the improvement (Z = −4.299, p < .001). Gains were uneven: where students had already answered most items correctly, movement was negligible; where they did not, correct responses rose sharply. Immersive media appear to work as targeted compensation for conceptual difficulty rather than general enrichment.